Formation of a Paradigm for Designing Cyber-Physical Systems: Educational Perspective - Glushchenko, Valery V. (Indonesian Journal of Teaching in Science, 2023)
The subject of the article is the process of forming a paradigm for designing cyber-physical systems. The object of the work is cyber-physical systems. the purpose of the work is to increase the efficiency of cyber-physical systems in the economy and society. To achieve this goal, the following tasks are solved: the formation of a paradigm for designing cyber-physical systems. descriptions of methodological provisions of the general theory of cyber-physical systems. descriptions of the factors generated by the general theory of cyber-physical systems to increase the effectiveness of such systems. General characteristics of methods of design and research of cyber-physical systems at all stages of their life cycle. description of the content of new academic disciplines in the field of design and research of cyber-physical systems. Methods of the article are philosophy and methodology of science, theory of hierarchical systems, theory modeling, historical and system analysis, and theory of technological structures. The scientific novelty of the article is associated with the formation of the design paradigm of cyber-physical systems and the creation of a general theory of cyber-physical systems.